Utilization of extracts from some aomatic plants for Prolonging the shelf life of toast bread - Asmaa Mohsen Mahmoud; Ahmed Mahmoud Alian; Sayed Saad Smuda; Fatma Ahmed Ali (2025)
This study aims to increase the shelf life of toast bread using some aromatic plant and spices ethanolic extracts such as (fennel, caraway, chamomile). The active plant substances in fennel, caraway, chamomile, and the produced toast bread were determined, and the polyphenol compounds in fennel, caraway and chamomile were identified by chromatographic analysis. Also, The total phenolic contents and the antioxidant activities of studied aromatic plants extracted with different solvent were determined. The chemical composition of fennel powder, caraway powder, chamomile flower powder, and the produced toast bread were also performed. The microbial activity and anti-cancer activity of the ethanolic extracts of (fennel, caraway, chamomile) were determined. Meanwhile the physical properties and sensory evaluation of toast bread were determined. The results showed that caraway fruits powder contained a high percentage of protein compared to fennel and chamomile powder. The results related to amino acids also showed that caraway contains the highest percentage of amino acids except for proline and methionine, as their content was higher in chamomile, while fennel showed the lowest percentage of all amino acids. As for the results related to fatty acids, it was found that the selected aromatic plants (fennel, caraway and chamomile) are rich sources of essential unsaturated fatty acids (such as oleic acid, linoleic acid and linolenic acid) which are required for normal health diet more than saturated fatty acids. All the results obtained by estimating antioxidant activity using different methods (DPPH, ABTS, FRAP) showed that caraway is rich in antioxidant activity compared to fennel and chamomile. Caraway and chamomile at a concentration of 10% showed their microbial activity on Candida tropiclis fungus as well as their effect on Gram-positive bacteria Bacillus subtilis compared to ethanolic extract of fennel. The results confirmed the effective effect of using caraway extract on anticancer activity in liver cancer cells, colon cancer cells and breast cancer cells. The shelf life of toast bread at normal temperature was also studied and tracked compared to using ethanolic extracts of fennel fruits powder, caraway fruits powder and chamomile flower powder at two different concentrations for each extract. The results confirmed that adding fennel seed powder extract, caraway fruits powder or chamomile seed powder increased the shelf life of toast bread up to 15 days. Therefore, it can be recommended to use ethanolic extracts of fennel, caraway and chamomile to extend the shelf life of the produced toast bread. It was found that levels of caraway (10 gm caraway extract/100 gm toast bread) had the lowest values of sensory evaluation.
(3JgOa gPg GdOQGSI Gdj RjGOI eOI UdGMjI MaX NHR GdJhSJ HGSJNOGe eSJNdUGJ fHGJjI ef HYV GdfHGJGJ GdYWQjI eKd (B((3GdTeQ GdcQGhjI, GRgGQ GdHGHhfL(B) (3Yf WQjb GdGSJNdGU GdGjKGfhdj(B. (3Je JMOjO GdehGO GdaYGdI GdfHGJjI aj HPhQ GdTeQ, GdcQGhjI, GdHGHhfL, hNHR GdJhSJ GdoefJL, hJe JMOjO eQcHGJ GdHhdj ajfhdGJ aj eSJNdUGJ GdGjJGfhdjI GdTeQ, GdcQGhjI, GdHGHhfL HhGSWI GdJMdjd GdcQheGJhLQGaj(B. (3ceG Je ELQGA GdJQcjH GdcjejGFj deSMhb GdTeQ, eSMhb GdcQGhjI, heSMhb GdHGHhfL, hNHR GdJhSJ GdoefJL(B. (3hJbOjQ GdfTGW GdejcQhHj hGdfTGW GdeVGO ddSQWGf deSJNdU GdGjKGfhdj dcd ef (B((3GdTeQ, GdcQGhjI, GdHGHhfL(B). (3HjfeG Je JMOjO GdNUGFU GdajRjGFjI hGdJbjje GdMSj ddNHR GdJhSJ(B. (3CXgQJ GdfJGFL Cf eSMhb HPhQ GdcQGhjI JMJhj Ydi fSHI YGdjI ef GdHQhJjf HGdebGQfI HeSMhb GdTeQ hGdHGHhfL(B. (3ceG CXgQJ GdfJGFL GdeJYdbI HGdGMeGV GdGejfjI Gf GdcQGhjI JMJhj Ydi CYdi fSHI ef GdCMeGV GdCejfjI HGSJKfGA GdHQhdjf hGdejKjhfjf, MjK cGfJ fSHI eMJhGgeG CYdi aj GdHGHhfL, HjfeG CXgQ GdTeQ Cbd fSHI ef LejY GdCMeGV GdCejfjI(B. (3GeG HGdfSHI ddfJGFL GdeJYdbI HGdGMeGV GdOgfjI hLO Gf GdCYTGH GdYWQjI GdeNJGQI (B((3GdTeQ hGdcQGhjI hGdHGHhfL(B) (3JYO eUOQkG ZfjkG HGdCMeGV GdOgfjI ZjQ GdeTHYI GdCSGSjI (B((3eKd MeV GdChdjc hMeV Gddjfhdjc hMeV Gddjfhdjfjc(B) (3hGdJj jJWdHgG GdfXGe GdZPGFj ddUMI GdWHjYjI CcKQ ef GdCMeGV GdOgfjI GdeTHYI(B. (3CXgQJ LejY GdfJGFL GdeJMUd YdjgG HJbOjQ fTGW GdeVGO ddCcSOI HGSJNOGe GdWQb GdeNJdaI (B(DPPH, ABTS, FRAP) (3Gf GdcQGhjI ZfjI HeVGOGJ GdGcSOI ebGQfI HGdTeQ hGdHGHhfL(B.(3GXgQJ cdG ef GdcQGhjI hGdHGHhfL HJQcjR (B10% (3fTGWgG GdejcQhHj Ydi NejQI (BCandida tropiclis (3hcPdc JCKjQge CjVG Ydi GdHcJQjG GdehLHI dLQGe (BBacillus subtilis (3ebGQfI HGdeSJNdU GdGjKGfhdj ddTeQ(B. (3CcOJ GdfJGFL Ydit GdKGKjQ GdaYGd dGSJNOGe eSJNdU GdcQGhjI Ydi GdfTGW GdeVGO ddSQWGf aj NdGjG SQWGf GdcHO, hNdGjG SQWGf Gdbhdhf, hNdGjG SQWGf GdKOj(B. (3ceG Gfg Je OQGSI hJJHY eOI MaX JNRjf NHR GdJhSJ aj OQLI GdMQGQI GdYGOjI ebGQfI HGSJNOGe eSJNdUGJ GdGjKGfhdjI dcdG ef (B((3GdTeQ, GdcQGhjI, GdHGHhfL(B) (3hPdc HJQcjRjf eNJdajf dcd eSJNdU efgeG(B. (3hbO hLO Cf eSJhjGJ GdcQGhjI (B(10 (3Le eSJdNU GdcQGhjI(B/ 100 (3Le NHR JhSJ(B) (3MUdJ Ydi Gbd bje GdJbjje GdMSj(B. (3CcOJ GdfJGFL Ydit Cf EVGaI eSJNdU eSMhb Cj ef GdTeQ, Gh GdcQGhjI Gh GdHGHhfL Ydj RjGOI MaX NHR GdJhSJ JUd Gdj deOI (B15 (3jhe(B. (3dPdc, jecf GdJhUjI HESJNOGe eSJNdUGJ GjKGfhdjI ef cdG ef eSMhb GdTeQ, heSMhb GdcQGhjI heSMhb GdHGHhfL dEWGdI eOI MaX NHR GdJhSJ GdoefJL(B.s
Thesis (M.Sc.)-Cairo University, 2025.
Bibliography: pages 90-107.
Issues also as CD.
Text in English and abstract in Arabic & English.
Keywords: Bread; (3GdNHRs; Fennel -- Chamomile -- Caraway -- Herbs -- Antioxidants -- Total phenolic content (TPC) -- Toast bread